The world''s largest oil and gas hydrocarbon deposits: rosa database and GIS project development - Odintsova A.; Gvishiani A.; Nakicenovic N.; Rybkina A.; Busch S.; Nikolova J. (Федеральное государственное бюджетное учреждение науки Геофизический центр Российской академии наук, 2018)
This article proposes the use of Big Data principles to support the future extraction of hydrocarbon resources. It starts out by assessing the possible energy-system transformations in order to shed some light on the future need for hydrocarbon resource extraction and corresponding drilling needs. The core contribution of this work is the development of a new database and the corresponding GIS (geographic information system) visualization project as basis for an analytical study of worldwide hydrocarbon occurrences and development of extraction methods. The historical period for the analytical study is from 1900 to 2000. A number of tasks had to be implemented to develop the database and include information about data collection, processing, and development of geospatial data on hydrocarbon deposits. Collecting relevant information made it possible to compile a list of hydrocarbon fields, which have served as the basis for the attribute database tables and its further filling. To develop an attribute table, the authors took into account that all accumulated data features on hydrocarbon deposits and divided them into two types: static and dynamic. Static data included the deposit parameters that do not change over time. On the other hand, dynamic data are constantly changing. Creation of a web service with advanced functionality based on the Esri Geoportal Server software platform included search by parameter presets, viewing and filtering of selected data layers using online mapping application, sorting of metadata, corresponding bibliographic information for each field and keywords accordingly. The collected and processed information by ROSA database and GIS visualization project includes more than 100 hydrocarbon fields across different countries.
Keywords: DATABASE; EXTRACTION; EXPLORATION; SYSTEM ANALYSIS; OIL AND GAS DEPOSITS; GIS PROJECT; CO2 STORAGE; DRILLING NEEDS